1983
DOI: 10.1007/bf01338893
|View full text |Cite
|
Sign up to set email alerts
|

Electric field effects on bacteria and yeast cells

Abstract: Comparative studies were carried out describing the lethal effects of electric pulses on GRAM-negative bacteria, GRAM-positive bacteria, and yeast cells. Microorganisms are killed by the pulse treatment without visible morphological destruction. The observed survival rates are figured as functions of the field strength E and the treatment time t (pulse number X time constant) revealing three explicit parameters as sufficient to explain the kinetics of the results. These parameters are determined by the species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
142
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(150 citation statements)
references
References 20 publications
5
142
0
3
Order By: Relevance
“…Further increase in the pulse width up to 125 ls had no statistically significant effect on the cell vitality; however, at the 150-ls pulse width, the culture contained already 35% necrotic cells. Hülsheger et al [27] reported over 99.99% inactivation of microorganisms exposed to peak electric fields of 20 kV/cm and pulses of several milliseconds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further increase in the pulse width up to 125 ls had no statistically significant effect on the cell vitality; however, at the 150-ls pulse width, the culture contained already 35% necrotic cells. Hülsheger et al [27] reported over 99.99% inactivation of microorganisms exposed to peak electric fields of 20 kV/cm and pulses of several milliseconds.…”
Section: Resultsmentioning
confidence: 99%
“…The electric field can affect the cell membranes [21], which can irreversibly be damaged [22][23][24], influences the transport of ions [25] and structure of enzymes [26]. In a cell subjected to PEF-induced transmembrane tension facilitates the formation of pores in the membrane and leads to an increase in its permeability [27][28][29][30][31]. Electroporation temporarily eliminates integrity of the plasmatic membrane, i.e., produces small pores that close back with a time [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Liong and Shah [23] reported growth of Lactobacillus bulgaricus and Lactobacillus acidophilus to be predominant in the first 9 -15 h after which it reached a stationary phase. Simova et al [24] analyzed the growth characteristics of Streptococcus thermophilus T15 and L. bulgaricus HP1 by pre-incubating both cultures for 5.5 h before inoculation and reported that growth reached exponential phase in the first 5 h and stationary phase in 8 -12 h. Hülsheger et al [25] reported that the application of electric fields to E. coli cells increased their survival in the exponential phase of growth. In addition, Kobayashi et al [26] has demonstrated that low intensity of pulsed ultrasound treatments stimulates cell proliferation and production of proteoglycan in human nucleus pulposus cell line, possibly by enhancement of growth factor-related genes.…”
Section: Growthmentioning
confidence: 99%
“…The efficacy of a high intensity PEF treatment strongly increases with increasing electric field strength (E) (Álvarez et al, 2003a;Heinz et al, 2002;Hülsheger, Potel & Niemann, 1981;Hülsheger, Potel & Niemann, 1983;. It is suggested that this increased efficacy only occurs, when the external applied electric field strength E exceeds the critical electric field strength (E c ) (Álvarez, Condón & Raso, 2006).…”
Section: Processing Parametersmentioning
confidence: 99%
“…High intensity PEFs can inactivate vegetative bacterial cells, yeasts and moulds, although differences in sensitivity towards the PEF treatment are observed between microorganisms (Hülsheger, Potel & Niemann, 1983;Raso et al, 1998;Toepfl, Heinz & Knorr, 2007b). It has been suggested that the morphology of the micro-organism plays a role in its sensitivity to high intensity PEF treatment (Heinz et al, 2002).…”
Section: Microbial and Culture Characteristicsmentioning
confidence: 99%